The Effects of Theta and Gamma tACS on Working Memory and Electrophysiology - Pahor, Anja; Jaušovec, Norbert (Frontiers in Human Neuroscience, 2018)
A single blind sham-controlled study was conducted to explore the effects of theta and gamma tACS on offline performance on working memory tasks. In order to systematically investigate how specific parameters of tACS affect working memory, we manipulated the frequency of stimulation (theta frequency vs. gamma frequency), the type of task (n-back vs. change detection task) and the content of the tasks (verbal vs. figural stimuli). A repeated measures design was used that consisted of 3 sessions: theta tACS, gamma tACS and sham tACS. In total, 4 experiments were conducted which differed only with respect to placement of tACS electrodes (bilateral frontal, bilateral parietal, left fronto-parietal, and right-fronto parietal). Healthy female students (N=72) were randomly assigned to one of these groups, hence we were able to assess the efficacy of theta and gamma tACS applied over different brain areas, contrasted against sham stimulation. The pre-post/sham resting EEG analysis showed that theta tACS significantly affected theta amplitude, whereas gamma tACS had no significant effect on EEG amplitude in any of the frequency bands of interest. Gamma tACS did not significantly affect working memory performance compared to sham, and theta tACS led to inconsistent changes in performance on the n-back tasks. Active theta tACS significantly affected P3 amplitude and latency during performance on the n-back tasks in the bilateral parietal and right-fronto parietal protocols.